Design of a simple coronary impedance simulator for the in vitro study of the complex coronary hemodynamics. (24th November 2016) - Piola, Marco; Vismara, Riccardo; Tasca, Giordano; Lucherini, Federico; Redaelli, Paola; Soncini, Monica; Romagnoni, Claudia; Mangini, Andrea; Antona, Carlo; Fiore, Gianfranco Beniamino
Abstract: Several novel approaches were recently developed to treat aortic root pathologies. The alteration induced by some of these approaches to the biomechanics of the aortic root could possibly affect the coronary perfusion, compromising the procedural outcome. In this scenario, the need to replicate in vitro the coronary flow pattern in physiological and pathological conditions is becoming crucial for the functional assessment of novel devices and techniques. This article describes the design of an easy-to-use, left-and-right coronary impedance simulator, coupled with native aortic roots for in vitro pulsatile tests. Experiments were performed in order to assess the performances of the coronary impedance simulator when coupled with healthy aortic valves (cardiac output: 3.8 ± 0.26 l min −1 ; mean systemic pressure: 95 ± 1.3 mmHg; mean coronary flow rate: 272 ± 13.4 ml min −1 ) or with regurgitant valves (cardiac output: 1.9 ± 0.24 l min −1 ; mean systemic pressure of 45 ± 3.3 mmHg; mean coronary flow rate:149 ± 21.9 ml min −1 ). The acute systemic response to valve regurgitation was also replicated, with increased beat rate and afterload, aimed at restoring the systemic pressure (cardiac output: 2.5 ± 0.23 l min −1 ; mean systemic pressure of 109 ± 6.1 mmHg; mean coronary flow rate: 262 ± 35.5 ml min −1 ). In the test conditions, the system was able to replicate in vitro the main determinants of the coronary circulation with physiological left/right coronary flow rate repartition, and a realistic interaction between coronary and systemic hemodynamics. The coronary simulator appears to be a suitable platform to study and optimize the interactions between novel approaches to aortic valve pathology and the coronary perfusion.